Pengaruh Pelatihan, Kompensasi Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Second Best Packing (SBP) Mojokerto - Hanik Uswatul Munawaroh; Abdul Kodir Djaelani; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine and explain the Influence Of Training, Compensation And Work Motivation On Employee Performance At Pt. Second Best Packing (Sbp) Mojokerto. This type of research includes is quantitative. Data analysis used is multiple linear regression. Determination of the sample using the formula slovin and obtained a sample of 72 respondents. To solve the problems in this study using SPSS with the help of validity test, reliability test, normality test, multiple linear regression analysis, multicollinearity test, heteroscedasticity test, F test, and t test. The results showed that simultaneously. The variables Training, Compensation, Work Motivation , significant simultaneously significant effect on Employee Performance (Y). And there is a partial influence between the Effect Of Training (X1), Compensation (X2) Work Motivation (X3), Employee Performance (Y)  Keywords: Training (X1), Compensation (X2) Work Motivation (X3), Employee Performance (Y)